Habitat Selection and Population Density of Diurnal and Nocturnal Lemurs in the Anjozorobe-Angavo Protected Area, Madagascar - Giulia Sassoli; Aurelia Sebastiani; Davide Mirante; Hanitriniaina Raharinirina; Rojotiana N. Rakotoarisoa; N. M. Koloina Rakotoarivelo; Fanomezantsoa L. Ravololoniaina; H. Domohina S. Randrianarisoa; Gabriele Ferraro; S. Jacques Rakotondranary; Timothy M. Eppley; Luca Santini (International Journal of Primatology, 2026)
Primates are among the most threatened mammals globally owing to rapid habitat loss and intense hunting pressure. Among these, lemurs are the taxon with the highest number of species at risk of extinction. Although many lemur species have been surveyed extensively across Madagascar, some taxa and protected areas remain understudied. The Anjozorobe-Angavo Protected Area, a rainforest landscape in the highlands of central-eastern Madagascar, has received relatively little ecological attention and continues to experience deforestation. This study was designed to estimate the population density and habitat selection of diurnal and nocturnal lemur species within La Mananara, a privately owned forest within Anjozorobe-Angavo. We conducted line-transect surveys over a 3-month period, between October and December 2024, and applied distance sampling to estimate species abundance. We also collected data on species detection locations and established vegetation plots to characterize habitat structure and evaluate species-specific habitat associations through resource selection functions. We recorded four diurnal and six nocturnal lemur species. Nocturnal species exhibited higher estimated densities and were more frequently encountered in areas with human activity, whereas diurnal species were less abundant and generally showed stronger associations with areas characterized by greater canopy cover and lower anthropogenic disturbance. Our findings underscore the conservation importance of primary forest protection, while also demonstrating the role of edge habitat and human-modified habitats for certain nocturnal taxa. These density estimates represent a quantitative assessment for this area, helping to inform the management of La Mananara, and contributing to broader conservation assessments of lemur populations within this under-characterized protected landscape.

Seismically triggered anoxia and brine spillover during the CE 365 Crete mega-earthquake in the eastern Mediterranean Sea - A. Polonia; A. Asioli; L. Ferraro; E. Colizza; F. Corticelli; G.J. de Lange; A. Gallerani; G. Gasparotto; L. Gasperini; G. Giorgetti; V. La Cono; G. La Spada; et al. (Gondwana Research, 2026)

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Rewilding relationships: Principles for forging relationships in social-ecological systems - Kristy M. Ferraro; Toryn Whitehead (Ambio, 2026)
Rewilding deliberately forges new relationships within complex socio-ecological systems. Yet, many rewilding initiatives proceed without fully considering the multitude of relationships at play. In this paper, we advance a framework that reimagines rewilding as a relationship-centered process, emphasizing that success depends on fostering connections from individual to collective levels for humans and non-humans alike. To illustrate this, we focus on species (re)introductions, identifying the various collective and individual relationships that shape rewilding outcomes. We then propose five principles for effectively forging these relationships: (1) reconsider values and perceptions of nature; (2) embrace a collective and individual-oriented approach; (3) place local communities at the heart of rewilding initiatives; (4) cautiously revive lost relationships; and (5) strengthen the connection between science and policy. Our framework demonstrates that identifying and fostering these relationships is not just essential but transformative, paving the way for rewilding practitioners to create ethical, interconnected, and resilient socio-ecological systems.

Zoogeochemical niche construction: how animal-mediated biogeochemistry affects evolution - Kristy M. Ferraro; Shawn J. Leroux; Mark A. Bradford; Oswald J. Schmitz; Eric Vander Wal (Trends in Ecology & Evolution, 2025)

Detection of Dengue virus RNA in Wastewater during a Local Epidemic in Central Italy (August–October 2024) - P. Mancini; C. Veneri; G. Bonanno Ferraro; A. Franco; M. Iaconelli; D. Brandtner; L. Lucentini; G. Venturi; E. Mancuso; G. Marsili; M. Del Manso; C. Sacco; et al. (Food and Environmental Virology, 2025)

The use and abuse of ecosystem service concepts and terms - Kristy M. Ferraro; Anthony L. Ferraro; Erick Lundgren; Nathalie R. Sommer (Biological Conservation, 2025)

Nitrogen uptake and associated pH changes influence growth and biomass composition in microalgae from a polluted river - V. Passucci; M. M. Areco; G. Ferraro; G. Curutchet (International Journal of Environmental Science and Technology, 2025)

Sedimentological and biostratigraphic reconstruction of the Early Pleistocene San Giuliano Lake section (Matera, Southern Italy) - F.O. Amore; C. Argenio; C. Faranda; L. Ferraro; E. Gliozzi; D. Magri; F. Michelangeli; B. Russo; J. Siciliano; M. Vallefuoco; A. Mauro; A. Meo; et al. (Quaternary International, 2025)

Climate change and occupational health and safety. Risk of injuries, productivity loss and the co-benefits perspective - A. Marinaccio; C. Gariazzo; L. Taiano; M. Bonafede; D. Martini; S. D'Amario; F. de’Donato; M. Morabito; Filippo Ariani; Alessandra Binazzi; Andrea Bogi; Michela Bonafede; et al. (Environmental Research, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Publisher Correction: Business-as-usual trends will largely miss 2030 global conservation targets - Ignacio Palomo; Alberto González-García; Paul J. Ferraro; Roldan Muradian; Unai Pascual; Manuel Arboledas; James M. Bullock; Enora Bruley; Erik Gómez-Baggethun; Sandra Lavorel (Ambio, 2025)

Business-as-usual trends will largely miss 2030 global conservation targets - Ignacio Palomo; Alberto González-García; Paul J. Ferraro; Roldan Muradian; Unai Pascual; Manuel Arboledas; James M. Bullock; Enora Bruley; Erik Gómez-Baggethun; Sandra Lavorel (Ambio, 2025)
To address climate change and global biodiversity loss, the world must hit three important international conservation targets by 2030: protect 30% of terrestrial and marine areas, halt and reverse forest loss, and restore 350 Mha of degraded and deforested landscapes. Here, we (1) provide estimates of the gaps between these globally agreed targets and business-as-usual trends; (2) identify examples of rapid past trend-shifts towards achieving the targets; and (3) link these past trend-shifts to different levers. Our results suggest that under a business-as-usual scenario, the world will fail to achieve all three targets. However, trend-shifts that rapidly “bend the curve” have happened in the past and these should therefore be fostered. These trend-shifts are linked to transformative change levers that include environmental governance, economic factors, values, and knowledge. Further research on trend-shifts, as well as bold action on underlying levers, is urgently needed to meet 2030 global conservation targets.

Global quantification and distribution of antibiotic resistance genes in oceans and seas: Anthropogenic impacts and regional variability - G. Bonanno Ferraro; D. Brandtner; A. Franco; M. Iaconelli; P. Mancini; C. Veneri; R. Briancesco; A.M. Coccia; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; et al. (Science of The Total Environment, 2024)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

The biogeochemical boomerang: Site fidelity creates nutritional hotspots that may promote recurrent calving site reuse - Kristy M. Ferraro; Dara Albrecht; Jack G. Hendrix; Eric Vander Wal; Oswald J. Schmitz; Quinn M. R. Webber; Mark A. Bradford (Ecology Letters, 2024)
Animals interact with nutrient cycles by consuming and depositing nutrients, interactions studied separately in nutritional ecology and zoogeochemistry. Recent theoretical work bridges these disciplines, highlighting that animal‐driven nutrient recycling could be crucial in helping animals meet their nutritional needs. When animals exhibit site fidelity, they consistently deposit nutrients, potentially improving vegetation quality. We investigated this potential feedback by analysing changes in forage nitrogen stocks following simulated caribou calving. We found that forage nitrogen stocks increased after 2 weeks and remained elevated after 1 year, a change due to increased forage quality, not quantity. We also developed a nutrient budget within calving grounds, demonstrating that natal fluid and calf carcasses contribute substantial nitrogen subsidies. We, thus, highlight a positive zoogeochemical feedback whereby nutrients deposited during calving become bioavailable during lactation and provide evidence that site fidelity creates a biogeochemical boomerang in which animals deposit nutrients that can be reused later.

Individuals in focus: Individuals as the ecological and ethical center of human-wildlife conflict - Kaggie D. Orrick; Kristy M. Ferraro; Nathalie R. Sommer (Biological Conservation, 2024)

Plant functional type shapes nitrogen availability in a regenerating forest - Les Welker; Elisabeth B. Ward; Mark A. Bradford; Kristy M. Ferraro (Plant and Soil, 2024)

Detection and full genomic sequencing of rare hepatitis E virus genotype 4d in Italian wastewater, undetected by clinical surveillance - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; C. Del Giudice; A.R. Ciccaglione; R. Bruni; M. Equestre; C. Marcantonio; E. Suffredini; G. La Rosa (Science of The Total Environment, 2024)

Tracing the footprints of SARS-CoV-2 in oceanic waters - Giuseppina La Rosa; P. Mancini; M. Iaconelli; C. Veneri; G. Bonanno Ferraro; C. Del Giudice; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; M. Martuzzi; A. Piccioli (Science of The Total Environment, 2024)

Fermentative hydrogen production enhancement by microbial community selection and enrichment through biostimulation - G. Policastro; A. Ferraro; V. Mazzurco Miritana; G. Massini; M. Fabbricino (Fuel, 2024)

Faecal nutrient deposition of domestic and wild herbivores in an alpine grassland - Laura Barbero-Palacios; Kristy M. Ferraro; Isabel C. Barrio; Jennifer A. Krumins; Jordi Bartolomé; Elena Albanell; Laia Jarque-Bascuñana; Santiago Lavín; Juan A. Calleja; José A. Carreira; Emmanuel Serrano (Science of The Total Environment, 2023)

Revisiting two dogmas of conservation science - Kristy M. Ferraro; Anthony L. Ferraro; A. Z. Andis Arietta; Nathalie R. Sommer (Conservation Biology, 2023)
Conservation science is a morally motivated field, with implicit and explicit values built into its practice. As such, conservationists must engage with conservation ethics to interrogate underlying values. We examine cutting‐edge ecological science and contemporary ethics to revisit two conservation norms that have become dogmatic in the field: ecological collectives, but not individual animals, are valuable and anthropomorphism should be staunchly avoided. Emerging studies demonstrate that individuals and their intraspecific variation can be instrumentally valuable for conservation science, and there is an emerging consensus within environmental philosophy around the moral worth of individuals. Thus, we suggest conservation science should explicitly recognize the value of individuals. We also argue that avoiding anthropomorphism is detrimental to conservation because critical anthropomorphism enables a more nuanced scientific approach—allowing conservationists to ask enlightened questions with creativity and compassion. We provide evidence that both dogmatic norms are scientifically and morally outdated and propose new normative values to push conservation towards more robust science and ethical practice.

Bovine lead exposure from informal battery recycling in India - Gregory Ferraro; Bret Ericson; Andrew M. Simons; Emily Nash; Mohammed Kabir (Environmental Science and Pollution Research, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

What killed the rarest snake in North America? - Kevin M. Enge; Jaimi A. Gray; Coleman M. Sheehy; Trudy Ferraro; Drew M. Martin; Jonathan D. Mays (Ecology, 2023)

A State-of-the-Art Scoping Review on SARS-CoV-2 in Sewage Focusing on the Potential of Wastewater Surveillance for the Monitoring of the COVID-19 Pandemic - G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; E. Suffredini; L. Bonadonna; L. Lucentini; A. Bowo-Ngandji; C. Kengne-Nde; D. S. Mbaga; G. Mahamat; H. R. Tazokong; et al. (Food and Environmental Virology, 2022)

Hepatitis E Virus in Water Environments: A Systematic Review and Meta-analysis - G. R. Takuissu; S. Kenmoe; L. Ndip; J. T. Ebogo-Belobo; C. Kengne-Ndé; D. S. Mbaga; A. Bowo-Ngandji; M. G. Oyono; R. Kenfack-Momo; S. Tchatchouang; J. Kenfack-Zanguim; R. Lontuo Fogang; et al. (Food and Environmental Virology, 2022)
Hepatitis E virus (HEV) is responsible for acute hepatitis in humans, through foodborne, zoonotic, and waterborne transmission routes. This study aimed to assess the prevalence of HEV in water matrices. Six categories were defined: untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse). We searched PubMed, Web of Science, Global Index Medicus, and Excerpta Medica Database. Study selection and data extraction were performed by at least two independent investigators. Heterogeneity ( I 2 ) was assessed using the χ 2 test on the Cochran Q statistic and H parameter. Sources of heterogeneity were explored by subgroup analysis. This study is registered with PROSPERO, number CRD42021289116. We included 87 prevalence studies from 58 papers, 66.4% of which performed in Europe. The overall prevalence of HEV in water was 9.8% (95% CI 6.4–13.7). The prevalence was higher in untreated wastewater (15.1%) and lower in treated wastewater (3.8%) and in drinking water (4.7%). In surface water, prevalence was 7.4%, and in groundwater, the percentage of positive samples, from only one study available, was 8.3%. Overall, only 36.8% of the studies reported the genotype of HEV, with genotype 3 (HEV-3) prevalent (168 samples), followed by HEV-1 (148 sample), and HEV-4 (2 samples). High-income countries were the most represented with 59/87 studies (67.8%), while only 3/87 (3.5%) of the studies were performed in low-income countries. The overall prevalence obtained of this study was generally higher in industrialized countries. Risk of bias was low in 14.9% of the studies and moderate in 85.1%. The results of this review showed the occurrence of HEV in different waters environments also in industrialized countries with sanitation and safe water supplies. While HEV transmission to humans through water has been widely demonstrated in developing countries, it is an issue still pending in industrialized countries. Better knowledge on the source of pollution, occurrence, survival in water, and removal by water treatment is needed to unravel this transmission path. Graphical Abstract

The search for blue transitions in aquaculture‐dominant countries - Richard S. Cottrell; Danielle M. Ferraro; Gordon D. Blasco; Benjamin S. Halpern; Halley E. Froehlich (Fish and Fisheries, 2021)
The capacity for aquaculture to provide an alternative source of fish and seafood to capture fisheries was once promoted as a tool to reduce demand for wild fish and thus tackle overfishing. To date, there is little evidence to suggest that aquaculture growth has successfully reduced fishing effort on wild populations. Recent theory on “blue transitions” suggests that displacement may only occur as aquaculture production surpasses that of capture operations. Yet, there has been no systematic attempt to understand whether aquaculture‐driven fisheries displacement has occurred in countries where aquaculture is now the dominant production form. We investigate the role of aquaculture on fisheries landings in these “aquaculture‐dominant” countries using national‐level production, trade, consumption and socioeconomic data from 1980 to 2017. Importantly, we find that aquaculture growth is associated with fisheries decline in aquaculture‐dominant countries, but the marginal effects of aquaculture have a far weaker influence on wild‐caught landings than other promoting factors, such as fish consumption and trade. Further, our qualitative analysis of the state of wild fisheries in aquaculture‐dominant nations suggests that overexploitation continues to be pervasive and that any minimal displacement effects from aquaculture are unlikely to have offset the environmental impacts imposed by the growing sector. The rise of aquaculture as an alternative production form can provide valuable insights for growing industries developing sustainable new foods. Unless coupled with effective food consumption policy, such products may simply add to rather than displace the environmental impacts of human food production.

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.

Pepper Mild Mottle Virus as Indicator of Pollution: Assessment of Prevalence and Concentration in Different Water Environments in Italy - G. Bonanno Ferraro; E. Suffredini; P. Mancini; C. Veneri; M. Iaconelli; L. Bonadonna; M. T. Montagna; O. De Giglio; G. La Rosa (Food and Environmental Virology, 2021)

Substantial Gaps in the Current Fisheries Data Landscape - Gordon D. Blasco; Danielle M. Ferraro; Richard S. Cottrell; Benjamin S. Halpern; Halley E. Froehlich (Frontiers in Marine Science, 2020)
Effective management of aquatic resources, wild and farmed, has implications for the livelihoods of dependent communities, food security, and ecosystem health. Good management requires information on the status of harvested species, yet many gaps remain in our understanding of these species and systems, in particular the lack of taxonomic resolution of harvested species. To assess these gaps we compared the occurrence of landed species (freshwater and marine) from the United Nations Food and Agriculture Organization (FAO) global fisheries production database to those in the International Union for Conservation of Nature (IUCN) Red List and the RAM Legacy Stock Assessment Database, some of the largest and most comprehensive global datasets of consumed aquatic species. We also quantified the level of resolution and trends in taxonomic reporting for all landed taxa in the FAO database. Of the 1,695 consumed aquatic species or groups in the FAO database considered in this analysis, a large portion (35%) are missing from both of the other two global datasets, either IUCN or RAM, used to monitor, manage, and protect aquatic resources. Only a small number of all fished taxa reported in FAO data (150 out of 1,695; 9%) have both a stock assessment in RAM and a conservation assessment in IUCN. Furthermore, 40% of wild caught landings are not reported to the species level, limiting our ability to effectively account for the environmental impacts of wild harvest. Landings of invertebrates (44%) and landings in Asia (>75%) accounted for the majority of harvest without species specific information in 2018. Assessing the overlap of species which are both farmed and fished to broadly map possible interactions – which can help or hinder wild populations - we found 296 species, accounting for 12% of total wild landings globally, and 103 countries and territories that have overlap in the species caught in the wild and produced through aquaculture. In all, our work highlights that while fisheries management is improving in many areas there remain key gaps in data resolution that are critical for fisheries assessments and conservation of aquatic systems into the future.

The Effects of Calcium on Lipid–Protein Interactions and Ion Flux in the Cx26 Connexon Embedded into a POPC Bilayer - Juan M. R. Albano; Gabriel E. Jara; M. Laura Fernández; Julio C. Facelli; Marta B. Ferraro; Monica Pickholz (The Journal of Membrane Biology, 2019)

Occurrence and Genetic Diversity of Human Cosavirus in Sewage in Italy - G. Bonanno Ferraro; P. Mancini; M. Divizia; E. Suffredini; S. Della Libera; M. Iaconelli; G. La Rosa (Food and Environmental Virology, 2018)

Historical maps and satellite images as tools for shoreline variations and territorial changes assessment: the case study of Volturno Coastal Plain (Southern Italy) - I. Alberico; G. Cavuoto; V. Di Fiore; M. Punzo; D. Tarallo; N. Pelosi; L. Ferraro; E. Marsella (Journal of Coastal Conservation, 2018)

A multidisciplinary approach to study confined marine basins: the holobenthic and merobenthic assemblages in the Mar Piccolo of Taranto (Ionian Sea, Mediterranean) - L. Ferraro; F. Rubino; M. Belmonte; S. Da Prato; M. Greco; F. Frontalini (Marine Biodiversity, 2017)

Phenotypic plasticity in freshwater picocyanobacteria - Paula Huber; Nadia Diovisalvi; Marcela Ferraro; Sebastián Metz; Leonardo Lagomarsino; María Eugenia Llames; Marta Royo‐Llonch; José Bustingorry; Roberto Escaray; Silvia G. Acinas; Josep M. Gasol; Fernando Unrein (Environmental Microbiology, 2017)
Summary Picocyanobacteria can occur as single‐cell (Pcy) or as colonies (CPcy). Published evidence suggests that some Pcy strains have the capability to aggregate under certain culture conditions, however this has not been demonstrated to occur in natural environments. We investigated whether the Pcy and CPcy belong to the same species (i.e. phylotype), and the factors that determine their morphological and genetic variability in a hypertrophic shallow lake dominated by picocyanobacteria. Six main different morphologies and >30 phylotypes were observed. All sequences retrieved belonged to the ‘ Anathece + Cyanobium ’ clade (Synechococcales) that are known to have the capability of aggregation/disaggregation. The temporal variation of picocyanobacteria morphotype composition was weakly correlated with the DGGE temporal pattern, and could be explained by the composition of the zooplankton assemblage. Laboratory experiments confirmed that the small cladoceran Bosmina favoured the dominance of CPcy, i.e. Cyanodictyon doubled the size of the colonies when present, most likely through the aggregation of single‐cell picocyanobacteria into colonies. Flow cytometry cell sorting and 16S rRNA + ITS sequencing of the Pcy and CPcy cytometrically‐defined populations revealed that some phylotypes could be found in both sorted populations, suggesting phenotypic plasticity in which various Synechococcales phylotypes could be found in situ either as single‐cells or as colonies.

Improving credibility and transparency of conservation impact evaluations through the partial identification approach - Matthew M. McConnachie; Claudia Romero; Paul J. Ferraro; Brian W. van Wilgen (Conservation Biology, 2016)
The fundamental challenge of evaluating the impact of conservation interventions is that researchers must estimate the difference between the outcome after an intervention occurred and what the outcome would have been without it (counterfactual). Because the counterfactual is unobservable, researchers must make an untestable assumption that some units (e.g., organisms or sites) that were not exposed to the intervention can be used as a surrogate for the counterfactual (control). The conventional approach is to make a point estimate (i.e., single number along with a confidence interval) of impact, using, for example, regression. Point estimates provide powerful conclusions, but in nonexperimental contexts they depend on strong assumptions about the counterfactual that often lack transparency and credibility. An alternative approach, called partial identification (PI), is to first estimate what the counterfactual bounds would be if the weakest possible assumptions were made. Then, one narrows the bounds by using stronger but credible assumptions based on an understanding of why units were selected for the intervention and how they might respond to it. We applied this approach and compared it with conventional approaches by estimating the impact of a conservation program that removed invasive trees in part of the Cape Floristic Region. Even when we used our largest PI impact estimate, the program's control costs were 1.4 times higher than previously estimated. PI holds promise for applications in conservation science because it encourages researchers to better understand and account for treatment selection biases; can offer insights into the plausibility of conventional point‐estimate approaches; could reduce the problem of advocacy in science; might be easier for stakeholders to agree on a bounded estimate than a point estimate where impacts are contentious; and requires only basic arithmetic skills.

Glyphosate input modifies microbial community structure in clear and turbid freshwater systems - H. Pizarro; M. S. Vera; A. Vinocur; G. Pérez; M. Ferraro; R. J. Menéndez Helman; M. dos Santos Afonso (Environmental Science and Pollution Research, 2016)

Cytoskeletal Alterations and Biomechanical Properties of parkin-Mutant Human Primary Fibroblasts - Daniele Vergara; Marzia M. Ferraro; Mariafrancesca Cascione; Loretta L. del Mercato; Stefano Leporatti; Anna Ferretta; Paola Tanzarella; Consiglia Pacelli; Angelo Santino; Michele Maffia; Tiziana Cocco; Ross Rinaldi; et al. (Cell Biochemistry and Biophysics, 2015)

Multi-center evaluation of the VITEK® MS system for mass spectrometric identification of non-Enterobacteriaceae Gram-negative bacilli - R. Manji; M. Bythrow; J. A. Branda; C.-A. D. Burnham; M. J. Ferraro; O. B. Garner; R. Jennemann; M. A. Lewinski; A. B. Mochon; G. W. Procop; S. S. Richter; J. A. Rychert; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pulmonary Inflammation and Cell Death in Mice After Acute Exposure to Air Particulate Matter From an Industrial Region of Buenos Aires - F. Astort; M. Sittner; S. A. Ferraro; N. S. Orona; G. A. Maglione; A. De la Hoz; D. R. Tasat (Archives of Environmental Contamination and Toxicology, 2013)

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Identification of Enterobacteriaceae by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry using the VITEK MS system - S. S. Richter; L. Sercia; J. A. Branda; C.-A. D. Burnham; M. Bythrow; M. J. Ferraro; O. B. Garner; C. C. Ginocchio; R. Jennemann; M. A. Lewinski; R. Manji; A. B. Mochon; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Current views on EDDS use for ex situ washing of potentially toxic metal contaminated soils - M. Fabbricino; A. Ferraro; G. Del Giudice; L. d’Antonio (Reviews in Environmental Science and Bio/Technology, 2013)

Oven-dried mosses as tools for trace element detection in polluted waters: A preliminary study under laboratory conditions - M. Cesa; A. Bizzotto; C. Ferraro; F. Fumagalli; P. Luigi Nimis (Plant Biosystems, 2011)

Recorded ground motion and site effects evaluation for the April 6, 2009 L’Aquila earthquake - M. Maugeri; A. L. Simonelli; A. Ferraro; S. Grasso; A. Penna (Bulletin of Earthquake Engineering, 2011)

Genotoxic evaluation of different doses of inorganic lead (PbII) in Hoplias malabaricus - W. A. Ramsdorf; M. V. M. Ferraro; C. A. Oliveira-Ribeiro; J. R. M. Costa; M. M. Cestari (Environmental Monitoring and Assessment, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Long term monitoring of oil spills in European seas - G. Ferraro; S. Meyer‐Roux; O. Muellenhoff; M. Pavliha; J. Svetak; D. Tarchi; K. Topouzelis (International Journal of Remote Sensing, 2009)

A Factor Influence Study of Trace Element Bioaccumulation in Moss Bags - M. Cesa; B. Campisi; A. Bizzotto; C. Ferraro; F. Fumagalli; P. L. Nimis (Archives of Environmental Contamination and Toxicology, 2008)

Burkholderia cepacia complex nasal isolation in immunocompetent patients with sinonasal polyposis not associated with cystic fibrosis - G. Marioni; R. Rinaldi; C. Staffieri; G. Ottaviano; R. Marchese-Ragona; L. Giacomelli; S. M. Ferraro; A. Staffieri (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

Fine mapping of a seizure susceptibility locus on mouse Chromosome 1: nomination of Kcnj10 as a causative gene - Russell J. Buono; Thomas N. Ferraro; Gregory T. Golden; George G. Smith; James F. Martin; Falk W. Lohoff; Tracy A. Gieringer; Deborah Zamboni; Candice L. Schwebel; Danielle M. Press; Stephanie Hongyu O. KratzerZhao; Wade H. Berrettini (Mammalian Genome, 2004)

Nest Poaching in Neotropical Parrots - Timothy F. Wright; Catherine A. Toft; Ernesto Enkerlin‐Hoeflich; Jaime Gonzalez‐Elizondo; Mariana Albornoz; Adriana Rodríguez‐Ferraro; Franklin Rojas‐Suárez; Virginia Sanz; Ana Trujillo; Steven R. Beissinger; Vicente Berovides A.; Xiomara Gálvez A.; et al. (Conservation Biology, 2001)
Although the poaching of nestlings for the pet trade is thought to contribute to the decline of many species of parrots, its effects have been poorly demonstrated. We calculated rates of mortality due to nest poaching in 23 studies of Neotropical parrots, representing 4024 nesting attempts in 21 species and 14 countries. We also examined how poaching rates vary with geographic region, presence of active protection programs, conservation status and economic value of a species, and passage of the U.S. Wild Bird Conservation Act. The average poaching rate across all studies was 30% of all nests observed. Thirteen studies reported poaching rates of ≥20%, and four reported rates openface> 70%. Only six studies documented no nest poaching. Of these, four were conducted on islands in the Caribbean region, which had significantly lower poaching rates than the mainland Neotropics. The other two studies that showed no poaching were conducted on the two species with the lowest economic value in our sample ( U.S. retail price). In four studies that allowed direct comparison between poaching at sites with active nest protection versus that at unprotected sites, poaching rates were significantly lower at protected sites, suggesting that active protection efforts can be effective in reducing nest poaching. In those studies conducted both before and after the passage of the U.S. Wild Bird Conservation Act, poaching rates were found to be significantly lower following its enactment than in the period before. This result supports the hypothesis that the legal and illegal parrot trades are positively related, rather than inversely related as has been suggested by avicultural interests. Overall, our study indicates that poaching of parrot nestlings for economic gain is a widespread and biologically significant source of nest mortality in Neotropical parrots.

Cytosine Methylation is Not Involved in the Heterochromatization of the Paternal Genome of Mealybug Planococcus citri - G. Buglia; V. Predazzi; M. Ferraro (Chromosome Research, 1999)

Effects of scopolamine on delayed-matching-to-sample and paired associates tests of visual memory and learning in human subjects: comparison with diazepam and implications for dementia - T. W. Robbins; J. Semple; R. Kumar; M. I. Truman; J. Shorter; A. Ferraro; B. Fox; G. McKay; K. Matthews (Psychopharmacology, 1997)

Verification of a scattering-based algorithm for estimating rainfall over the open ocean - J. S. Greene; M. L. Morrissey; R. R. Ferraro (Theoretical and Applied Climatology, 1997)

Almost equivalence of combinatorial and distance processes for discrimination in multielement images - M. Ferraro; D. H. Foster (Biological Cybernetics, 1991)

Le pollinosi da oleacee. Indagine aerobiologica nell'atmosfera della città di Palermo - I. Cricchio; M. Zambito; A. Ferraro; D. Minutella; S. Corrao; E. Fileccia; G. Passalacqua (Aerobiologia, 1987)